Feasibility of postural sway calculation in the equine athlete using wearable sensor technology - Egan, S.; McKeown, D.; McGrath, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Wearable sensor technologies have begun to revolutionise the fields of sport and health. While the use of these technologies are rapidly becoming the "norm" in areas such as sports performance analysis and physical activity monitoring, the field of equine sports has been slower to uptake. A huge opportunity exists to harness these technologies in the training of athletic horses. The aim of this study was to assess the feasibility of measuring postural sway using on-body inertial sensors. The long-term aim of this research would be to use this measure for longitudinal monitoring of fatigue/recovery of horses in the field. Methods: A body-worn inertial sensor containing a tri-axial accelerometer was attached to one healthy horse at the highest point of the croup (posterior iliac spine) using a custom made attachment. The aim was to capture a "quiet standing" trial lasting at least 40s. Three quiet standing trials were recorded. Acceleration data were sampled at 51.2 Hz and band-pass filtered between 0.1-10 Hz. The initial 5 seconds of data were removed, and the subsequent 45 seconds of data were considered for further analysis. Cumulative horizontal acceleration was calculated using the mediallateral (ML) and anteriorposterior (AP) acceleration vectors, by twice integrating the acceleration signal. Low frequency drift was reduced using a second-order polynomial fit and subtracting the mean amplitude of the signal before and after each integration procedure and then high pass filtered at 0.1 Hz. Results: Only one trial out of three was suitable for analysis due to the horse`s idiosyncratic standing movements. The ranges of AP and ML displacement (i.e. 0-80mm) produced a stabiliogram similar in shape, but differing in magnitude to previous work using force plates (Clayton and Nauwelaerts, 2012). This is expected, given the distance of the inertial sensors from the centre of pressure changes beneath the horse`s hoof. Discussion: The sensor set-up and capture protocol successfully detected "quiet" postural sway in the equine animal. Our experiment confirmed the challenge of consistently capturing quiet standing data of sufficient length. It would therefore be preferable to perform long-term monitoring of postural sway while the horse is `sleeping`, due to the animals sophisticated `stay apparatus`, allowing it to remain standing in a resting state. Such data could be used to monitor the state of health of the equine athletes` motor control system, similar to emerging approaches in human movement.